Electro-Acupuncture Attenuates Chronic Stress Responses via Up-Regulated Central NPY and GABAA Receptors in Rats - Yang, Yu; Yu, Haijie; Babygirija, Reji; Shi, Bei; Sun, Weinan; Zheng, Xiaojiao; Zheng, Jun (Frontiers in Neuroscience, 2021)
Stress can increase the release of corticotropin-releasing factor (CRF) in the hypothalamus, resulting in attenuation of gastric motor functions. In contrast, central neuropeptide Y (NPY) can reduce the biological actions of CRF, and in turn weaken stress responses. Although electroacupuncture (EA) at stomach 36 (ST-36) has been shown to have anti-stress effects, its mechanism has not yet been investigated. The effect of EA at ST-36 on the hypothalamus-pituitary-adrenal (HPA) axis and gastrointestinal motility in chronic complicated stress (CCS) conditions have not been studied and the inhibitory mechanism of NPY on CRF through the gamma-aminobutyric acid (GABA)A receptor need to be further investigated. A CCS rat model was set up, EA at ST-36 was applied to the bilateral hind limbs every day prior to the stress loading. Further, a GABAA receptor antagonist was intracerebroventricularly (ICV) injected daily. Central CRF and NPY expression levels were studied, serum corticosterone and NPY concentrations were analyzed, and gastric motor functions were assessed. CCS rats showed significantly elevated CRF expression and corticosterone levels, which resulted in inhibited gastric motor functions. EA at ST-36 significantly increased central NPY mRNA expression and reduced central CRF mRNA expression as well as the plasma corticosterone level, helping to restore gastric motor function. However, ICV administration of the GABAA receptor antagonist significantly abolished these effects. EA at ST-36 upregulates the hypothalamic NPY system. NPY may, through the GABAA receptor, significantly antagonize the overexpressed central CRF and attenuate the HPA axis activities in CCS conditions, exerting influences and helping to restore gastric motor function.